Drug Development and Safety (Pharmaceutical Science, 2024)
This book provides a detailed overview covering all aspects of drug development, from synthesis and manufacturing to delivery strategies, and ensuring a thorough understanding of the field. This book will show how new drugs are made. The chapters also give inside information on regulatory authorities so that drugs meet the necessary standards for quality. Drug Development and Safety effortlessly switches over to drug delivery technologies by exploring ground-breaking methods that are changing medicine forever. Controlled-release drug delivery systems represent some of the current breakthroughs while using nanoparticles for treating cancer stands among other recent therapeutic innovations. Each chapter has been authored by a leading scientist or expert in that particular field, and various viewpoints will be presented to provide a fuller understanding of the subjects concerning the safety of drugs. The book will be for chemists, pharmacists, and biologists, and it will be their only guide while navigating the challenging pharmaceutical science terrain.